A Model, Specifications and Sample Items for a Measure of Career Adaptability in Young Blue-Collar Workers - Knasel, Edward G. (Canadian Journal of Counselling and Psychotherapy, 1980)
This paper describes the development of specifications, illustrated by sample items, for an instrument designed to assess career adaptability (vocational maturity) among young adult blue-collar workers. The specifications and sample items were based on a review of the relevant literature and a series of semi-structured interviews. They were designed to make it possible for a Canadian team to develop and validate an indigenous instrument, suitable for use in either counselling practice or in research. Recommendations are made concerning future areas of research and development.